The "New Father" Between Ideals and Practices: New Masculinity Ideology, Gender Role Attitudes, and Fathers' Involvement in Childcare. (3rd August 2021) - Offer, Shira; Kaplan, Danny
Abstract: Current research demonstrates a gap between widely shared ideals of new fatherhood and men's limited participation in childcare. Previous studies treat gender attitudes primarily in terms of work and family roles. In contrast, this study centers on perceptions of masculinity as a broader cultural-ideological construct. Specifically, it focuses on "new masculinity ideology, " a previously unexplored masculinity perspective associated with values such as authenticity, emotional expressivity, and holistic self-awareness. Using a sample of around 1, 400 employed fathers in the United States drawn from the AmeriSpeak Panel conducted by the National Opinion Research Center, we examined how identification with new masculinity relates to gender role attitudes and three childcare involvement outcomes. Results from moderation analyses based on the computation of simple slopes show that new masculinity played an important role in emotional engagement and parental responsibility but not in routine care. New masculinity moderated the association between father involvement attitudes and childcare outcomes, suggesting that fathers who endorse this ideology are more likely to act in ways that are congruent with their inner beliefs. The breadwinning role appeared to remain important. This study highlights the ways in which the often confounded images of the "new man" and "new father" are conceptually distinct.